Mobile Devices for Arabic Learning in Junior High Schools: The Teachers’ Perspective - Albantani, Azkia Muharom; Rahmadi, Imam Fitri (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2020)
The present study aims to identify teachers' perceptions of mobile devices use in Arabic learning at junior high schools. Employed a qualitative method with a case study, 24 Arabic language teachers from various junior high schools in the South Tangerang City involved in this study selected by using a random sampling method. Based on the teacher perspectives, the results of the study reveal that the use of mobile devices facilitates students in understanding Arabic lessons and increase their motivation for learning. Time limitations and large classroom sizes were obstacles that decrease teachers’ interest to integrate mobile devices into classroom activities. Reading is by far the main language skill taught by teachers and there is a less focus on productive skills such as speaking and writing. The students have less attention and motivation for learning Arabic while the teachers have attempted to deal with this problem by several measures.The characteristic of Arabic language differs from each context. However, whether for inside or outside classroom activities, active methods are of particular importance for Arabic learning. Arabic teaching and learning practices facilitated by mobile devices require careful planning for a successful implementation lead to more active and effective learning of Arabic.